The Effect of 360-Degree Feedback System and Talent Management towards Employee Performance with Employee Development as Mediating Variable - Case Study Sector of Aviation in Indonesia - Lukman, Andi (International Journal of Psychosocial Rehabilitation, 2020)
The current operational record Of PT XYZ from 2014 to 2016 showed that a high number of complaints occurred which indicates one of the operational employee performances has not been fulfilled. Based on a pre-study, it has concluded there were three dominant factors affecting employee performance. These are the 360- degree feedback system, talent management, and employee development. The purpose of this research is to analyze the effect that the 360-degree feedback system and talent management have towards employee performance with employee development as a mediating variable. The population used in this research consists of 742 employees. The sample collecting technique used was the stratifying random technique obtaining 180 respondents at various positions within the company. The research methodology uses a quantitative method through surveys and collecting data from questionnaires. The data analysis technique used in this study is the Structural Equation Model (SEM AMOS version 22.0). The results of the study showed that the 360-degree feedback system had a positive effect towards employee performance, talent management had a positive and significant effect towards employee performance, 360-degree feedback system had a positive and significant effect towards employee development, talent management had a significant and positive effect towards employee development and employee development had a positive effect towards employee performance.